Enfants nomades au pays des Inuit Iglulik - Saladin d'Anglure, Bernard (Anthropologie et Sociétés, 1988)
Child-transfer in Iglulik Inuit CountryInuit groups have been the subject of extensive research on adoption and child-transfer. One such group, the Iglulik Inuit, is used to exemplify the importance of viewing these practices from a structuralist, holistic and dynamic perspective. It is furthermore important to recognize the central role played by these same practices in the social structure, characterized as it is by overlapping households and generations. A regulatory mechanism not only of filiation but of marriage as well, child transfer plays a crucial role in the social reproduction of both human life and the material conditions of life. The interrelationships signified by such transfers must be set against the larger context of individualism vs. collectivism; an antagonistic and complementary dichotomy which encompasses just as much the production of game animals as that of children. Even sexuality and human procreation do not escape from it. Shamans, as well as elders, seem to be particularly involved in this process " notably with respect to wife/husband exchange. " Should not more light be shed on this mediating element within society, an element for too long marginalized by social anthropology ? Enfants nomades au pays des Inuit IglulikÀ partir de l'exemple des Inuit Iglulik, l'un des groupes inuit ayant donné lieu aux recherches les plus poussées sur l'adoption et les transferts d'enfants, on fait ressortir l'importance de considérer ces pratiques avec une approche structurale, holiste et dynamique et de leur reconnaftre une place centrale dans la structure sociale, caractérisée par le chevauchement entre les unités résidentielles et entre les cohortes générationnelles. Mécanisme régulateur de la filiation tout autant que de l'alliance, ces transferts participent à la reproduction sociale de la vie humaine et des conditions matérielles de la vie.Les chevauchements qu'ils expriment relèvent du jeu antagoniste et complémentaire de l'individualisme et du collectivisme qui touche autant la production du ...